THE EFFECT OF WORK DISCIPLINE AND WORK MOTIVATION ONEMPLOYEE PERFORMANCE AT PT. PLN (PERSERO) UIW SULSELRABAR - Annidar Eka Saputri; Maat Pono; Nurdjanah Hamid (Program Studi Akuntansi Universitas Kristen Indonesia Paulus, 2023)
In the same way that the rest of Indonesia has been hit hard by the Covid-19 epidemic, so too has PT PLN (Persero) UIW Sulselrabar. Several companies, including PT PLN (Persero) UIW Sulselrabar, have instituted work-from-home policies in response to the pandemic. Naturally, this may have an effect on employees' ability to self-regulate and motivate themselves to provide their best efforts on the job. The effects of discipline and motivation on output both before and after the pandemic are the primary foci of this study. One hundred people will be used as the sample size in this quantitative investigation. Data was gathered using questionnaires and analyzed using SPSS version 25. The results (indicated by the four indicators of time pressure, efficiency, absenteeism, and accountability) show a positive correlation with the discipline variable. Therefore discipline and motivation at PT PLN (Persero) UIW Sulselrabar have a large and positive effect on productivity.